Story Ave [videorecording (DVD)] - Charles, Pierre; Inglish, Chuck (Kino Lorber, 2023)
South Bronx teen Kadir is a gifted visual artist who loses his way following the death of his younger brother. Overcome with grief and struggling with the pressures of school and family, he escapes into the thrilling yet dangerous world of graffiti gangs, seeking an outlet for the creative force threatening to explode out of him. To prove himself and join his neighborhood's ruling gang, Kadir tries to rob no-nonsense MTA conductor Luis on the Story Ave subway platform. He is caught off guard when Luis agrees to give Kadir the cash if he sits down to a meal with him. Following their conversation and the delicate, transformative friendship that grows out of it, Kadir sees for the first time how his artistic talent could lead to a better life.